Web-Based Library Information System - Yerezqy Bagus; Prasetyo, Hendy (PPM Telkom University, 2024)
Muh 4 Yogyakarta Middle School is still record the borrowing and returning of books in its library manually. This school haven’t yet store book data in a system causes many errors in data collection, one of which is data redundancy. Recording of borrowing and returning each book is still done manually, so the librarian must always check repeatedly. The aim of this research is to design and build a web-based library information system to overcome existing problems. This research uses the Unified Modeling Language (UML) development method. In design process this system uses class diagrams, use case diagrams and activity diagrams as well as applying programs using the CodeIgniter Framework and database storage in MySQL. The result of this research is a web-based library information system that can overcome problems in borrowing and returning books. System testing was carried out twice, namely using alpha and beta tests. Test results show that all features can be built and work well. Beta testing of 80% shows users strongly agree that this system is worth using